Writing practices in additional languages in Grade 7 classes in the Eastern Cape province - Hendricks, Monica Grace (My University, 2006)
This thesis analyses the classroom writing of learners in their additional languages at four differently resourced schools in the Eastern Cape Province of South Africa. The choice of languages on offer at schools and the medium of instruction seldom meet current language education policy requirements of additive bilingualism needed to support children’s home language and general cognitive growth. The central question of my study concerns how school writing practices contribute to the development of learners’ writing ability. The data collected and analysed in order to investigate this were all the regular classroom writing of Grade 7 children in Afrikaans, English and isiXhosa, where these were additional languages, not the children’s home language. My findings were that there is no check by the Education Department on whether schools meet the official national curriculum policy requirements with regard to the amount of curriculum time allocated to language. Also, that there is a mismatch between the languages on offer at schools and the home languages of learners, and teachers, which is not monitored. My key findings with regard to writing were that there are significant differences and inequalities in the amounts that learners write at these schools across Afrikaans, English and isiXhosa. Decontextualised grammar tasks predominate in what learners write in all three languages at all four schools. Children write relatively few extended texts, and these are mainly personal expressive texts which are unlikely to develop their ability to write abstract, context-reduced genres. Teachers’ neglect of impersonal formal and factual genres at all four schools makes it difficult for learners to experience the benefits of writing these genres – that these genres set the basis for the development of abstract cognitivelydemanding language proficiency and disciplinary knowledge. In the case of English, which is the commonest medium of instruction even though it is the home language of less than 10% of the population, this shortcoming is especially serious.
Faculty of Humanities School of Education 0201596p m.hendricks@ru.ac.za
Keywords: Language Education Policy; Classroom Writing; Additional Language; Writting Competence; Writing pedagogy School